Coronary artery lesions and the increasing incidence of Kawasaki disease resistant to initial immunoglobulin. (1st July 2016) - Kibata, Tetsuhiro; Suzuki, Yasuo; Hasegawa, Shunji; Matsushige, Takeshi; Kusuda, Takeshi; Hoshide, Madoka; Takahashi, Kazumasa; Okada, Seigo; Wakiguchi, Hiroyuki; Moriwake, Tadashi; Uchida, Masashi; Ohbuchi, Noriko; et al.
Abstract: Backgrounds: Kawasaki disease (KD) is a systemic vasculitis of childhood involving coronary arteries. Treatment for intractable cases at a higher risk of cardiac sequelae remains controversial. Methods: Clinical outcomes of KD patients diagnosed in Yamaguchi prefecture, Japan between 2003 and 2014 were analyzed using the medical records from all 14 hospitals covering the prefecture. The study included 1487 patients (male:female, 873:614; median age at diagnosis, 24 months). Results: The proportion of initial intravenous immunoglobulin (IVIG)-resistant patients increased from 7% to 23% during this decade, although no patients died. Twenty-four patients developed coronary artery lesions (CALs) over one month after the KD onset. The incidence of CAL in patients who received corticosteroid during the disease course (10/37; 27.0%) was higher than that in those who did not (14/1450; 0.97%, p = 2.0 × 10 − 35 ). Nine patients who responded to initial IVIG plus corticosteroids had no CAL. Conversely, IVIG-resistant patients with alternate corticosteroid therapy more frequently developed CAL than those without it (10/28; 35.7% vs. 5/194; 2.6%, p = 8.9 × 10 − 10 ). Multivariate analyses indicated corticosteroid therapy (p < 0.0001), hyperbilirubinemia (p = 0.0010), and a longer number of days before treatment (p = 0.0005) as risk factors associated with CAL over a month after onset. The odds ratio of corticosteroid use increased from 18.3 to 43.5 if the cases were limited to initial IVIG non-responders and corticosteroid free-IVIG responders. Conclusions: IVIG-failure has recently increased. The incidence of CAL increased in intractable cases with prolonged corticosteroid use. Corticosteroid may not be alternate choice for IVIG-failure to reduce the risk of cardiac sequelae.